Improving public service through AI-powered design in Tambangan Village, Semarang City - Noora Qotrun Nada; Setyoningsih Wibowo; Aris Tri Joko Harjanto; Febrian Murti Dewanto (Universitas Muhammadiyah Magelang, 2024)
Village officials play a crucial role in providing public services to the community. In the digital era, the use of information technology, particularly artificial intelligence (AI), is becoming increasingly important to improve the efficiency and quality of these services. This community service program aims to enhance the capacity of village officials in Tambangan Village, Semarang City, to utilize AI technology, especially in the field of graphic design. This community service activity was conducted in the form of a workshop, providing training and mentorship to village officials. The evaluation results showed a high level of participant satisfaction. As many as 70% of participants expressed high satisfaction with the overall program, while 67% were highly satisfied with their understanding of the material presented. These results indicate that this training program successfully enhanced the competence of village officials in utilizing AI technology to support their daily tasks.